DERİN BOYUN ENFEKSİYONU: BİR OLGU SUNUMU - DEVELİOĞLU, Ömer Necati and YELKEN, Kürşat and GÜLTEKİN, Erdoğan and KÜLEKÇİ, Mehmet (Cerrahpaşa Medical Journal, 2014)
Background.- Deep neck infections are less frequent today than in the past, but when they do occur they remain serious infections. These infections carry significant morbidity and mortality due to the proximity of the airway, mediastinum, and other vital structures. The correct treatment of these infections is an appropriate antimicrobial therapy and abscess drainage. Observation.- We present a clinical case of a deep neck infection which was mimicking hypopharyngeal carcinoma with unilateral vocal cord paralysis . It was necessary surgical treatment to drain it.